Public Aspirations and Complaints Information System: Improving the Quality of Public Complaints in Sidrap Regency - Herlina Sakawati; Wina Pratiwi Sukman; Sulmiah Sulmiah; Widyawati Widyawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Public assessments determine the quality of public services, so public complaints are needed to improve service quality. In making the management of public complaints more effective as expected by the government in Presidential Regulation no. 76/2013, the Sidenreng Rappang Regency Government has utilized technology, by creating. public aspirations and complaints information system (SIAPP), but until now, the complaint service is still experiencing problems. The socialization of program innovations and complaint procedures through the SIAPP program is not evenly distributed at every level of society. In addition, the SIAPP admin is less responsive in responding to public complaints. Based on this, this research was carried out to analyze the quality of public complaint services in Sidenreng Rappang Regency through the SIAPP application to support the creation of quality public services. Qualitative research methods, with a descriptive approach, were the researcher's choice. Research data was obtained through interviews, which were also strengthened from observations and literature studies. The data that has been obtained is analyzed by referring to the interactive model. The research results show that the quality of public complaints in Sidenreng Rappang Regency cannot be improved by using the SIAPP application because the standard operational procedures for SIAPP are not yet complete. Regional apparatus organizations are slow in following up on community complaints, and community data security is still weak when using the SIAPP application.